2022
DOI: 10.3390/rs14184487
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Object Detection Based on Improved EfficientDet

Abstract: Intelligent detection of marine organism plays an important part in the marine economy, and it is significant to detect marine organisms quickly and accurately in a complex marine environment for the intelligence of marine equipment. The existing object detection models do not work well underwater. This paper improves the structure of EfficientDet detector and proposes the EfficientDet-Revised (EDR), which is a new marine organism object detection model. Specifically, the MBConvBlock is reconstructed by adding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 53 publications
0
8
0
1
Order By: Relevance
“…Deep learning techniques are the most used algorithms when detecting underwater objects, and these algorithms do not work the same in air as in underwater environments due to the environmental properties mentioned before. Works like [27] proposed a method for improving object detection in underwater environments based on an improved Ef-ficientDet. That method modified the structure of the neural network and the results showed that the mean average precision (mAP) reached 92.82%.…”
Section: Related Workmentioning
confidence: 99%
“…Deep learning techniques are the most used algorithms when detecting underwater objects, and these algorithms do not work the same in air as in underwater environments due to the environmental properties mentioned before. Works like [27] proposed a method for improving object detection in underwater environments based on an improved Ef-ficientDet. That method modified the structure of the neural network and the results showed that the mean average precision (mAP) reached 92.82%.…”
Section: Related Workmentioning
confidence: 99%
“…The model's architecture proposed in 9 is based on the MobileNetV2 network 10 and the 4 th version of YOLO 11 and is able to achieve an approximate average Mean Average Precision (mAP) of 86% over two public image dataset with an inference speed exceeding 44 Frames Per Second (FPS). The authors in 12 developed an improved version of EfficientDet 13 and compared it to Faster RCNN, 14 YOLOv4 11 and other detectors on two underwater datasets containing images of underwater animals that are collected using ROVs and other resources. Another group of researchers 15 compared the performance of Faster RCNN, 14 YOLOv3, 16 YOLOv4 11 RetinaNet 17 and SSD 18 detectors on the RUIE dataset 19 and concluded that different detectors offers different trade-offs and that YOLOv3 is the best performing detector on this dataset.…”
Section: Related Workmentioning
confidence: 99%
“…However, it is known that DWConv can lead to a loss of information. To solve this problem, input features are expanded before applying DWConv [29]. This expansion step mitigates the potential loss of information.…”
Section: • Efficientnet B2mentioning
confidence: 99%